DESAIN ULANG KNALPOT RACING 3V3 GUNA MENINGKATKAN KINERJA MESIN YAMAHA RX KING - Reynold Andika Janaprasetya; Teng Sutrisno (Petra Christian University, 2014)
Two stroke motorcycle has a grat power, such as Yamaha RX King which is the study of the experimental material. In a two stroke motorcycles, the biggest contribution to power is exhaust.Research process of 3v3 exhaust used experimental methods, so need some tools and materials in the manufacture of exhaust. Performance test use dyno test analises.The making exhaust use formulas, these fomulas is taken from Gordon’s book. With these experiment are shown the engine performance improve up to 30%.